Removal of organic micropollutants from water by adsorption on thermo-plasma expanded graphite encapsulated into calcium alginate - Marco Cuccarese; Stijn W. H. Van Hulle; Ignazio M. Mancini; Salvatore Masi; Donatella Caniani (Journal of Environmental Health Science and Engineering, 2023)
Nowadays, public concern is focused on the degradation of water quality. For this reason, the development of innovative technologies for water treatment in view of (micro)pollutant removal is important. Indeed, organic (micro)pollutants, such as pharmaceuticals, herbicides, pesticides and plasticizers at concentration levels of μg L −1 or even ng L −1 are hardly removed during conventional wastewater treatment. In view of this, thermo-plasma expanded graphite, a light-weight innovative material in the form of a powder, was encapsulated into calcium alginate to obtain a granular form useful as filtration and adsorption material for removal of different pollutants. The produced material was used to remove atrazine, bisphenol-A, 17-α-ethinylestradiol and carbamazepine (at concentration levels of 125, 250 and 500 µg L −1 ) by top-down filtration. The effect of flow rate, bed depth and adsorbent composition was evaluated based on breakthrough curves. The experimental data was analysed with the Adams-Bohart model in view of scale-up. Under optimal conditions, removal and adsorption capacity of respectively about 21%, 21%, 38%,42%, 43 µg g −1 , 44 µg g −1 , 37 µg g −1 and 87 µg g −1 were obtained for atrazine, bisphenol, 17-α ethinylestradiol and carbamazepine when using 0.12 g of thermo-plasma expanded graphite to treat 200 mL at 500 µg L −1 (for each compound) of solution obtaining at contact time of 20 min. The granular form of TPEG obtained (GTPEG) by entrapping in calcium alginate results to have a good adsorbent property for the removal of carbamazepine, atrazine, bisphenol A and 17-α ethinylestradiol from water at concentration levels between 250 and 500 μg L −1 . Promising results confirm the adsorbent properties of TPEG and push-up us to investigate on its application and improve of its performance by evaluating different entrapping materials.